List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-003 1. LIST OF TRADE UNIONISTS & LABOUR PARTY MEMBERS: LABOUR PARTY BRANCHES W. Coles Cardiff, Chairman Splott LLY Dependant: Mr. & Mrs. Coles, 13 Adeline St., Splott, Cardiff. (10/-) T. Elliot Worthing, Br. Secretary Dependant: T. Bloor Miles Platting & M (ter L.P. Pres. LLY Federation Dependant: C. West Mitcham Asst .Sect. Also E.C. Home Counties Asso. Dependant: J. Henderson Melton Mowbray & Asfordby LLP Sec. Also member Melton D.L.P. Dependant: T. Evans Port Talbot Ord. member Dependant: A. Doran Glastonbury (Surrey) Ord. member Dependant: J. Mann Blackpool Delegate Talbot Ward Dependant: E. Bee N. Battersea DLP Ass. Sec. Church Ward. Dependant: A. Francis Reading Ord. member. Dependant: J. Mudie Dundee (6th ward) ord. member. Dependant: D. Crook N. Paddington L.P. ord. member Dependant: H. Smith Jesmond LP, Secretary. Dependant: Mrs. H. Smith, 3 Chandes St., Gateshead-on-Tyne. (£1-10-0) P. Keegan Hull L.P. Ord. member Dependant: *- Other L.P. members listed under Trade Unions. 292/946/34/193(i)